Natural Products and Bioprospecting - Liu, Jikai; Luo, Xiaodong; Puno, Pema-Tenzin.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer.)
Natural Products and Bioprospecting serves as an international forum for essential research on natural products and focuses on, but is not limited to, the following aspects: Natural products: isolation and structure elucidation Natural products: synthesis Biological evaluation of biologically active natural products Bioorganic and medicinal chemistry Biosynthesis and microbiological transformation Fermentation and plant tissue cultures Bioprospecting of natural products from natural resources All research articles published in this journal have undergone rigorous peer review. In addition to original research articles, Natural Products and Bioprospecting publishes reviews and short communications, aiming to rapidly disseminate the research results of timely interest, and comprehensive reviews of emerging topics in all the areas of natural products. It is also an open access journal, which provides free access to its articles to anyone, anywhere.
Keywords: Botanical chemistry; Bioorganic chemistry; Medicinal chemistry; Pharmacology; Botany; Food science; Plant Biochemistry; Bioorganic Chemistry; Medicinal Chemistry; Pharmacology; Plant Science; Food Science